2022
DOI: 10.1111/iju.14912
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a new electronic nose for prostate cancer diagnosis in urine samples

Abstract: To evaluate the accuracy of a new electronic nose to recognize prostate cancer in urine samples. Methods: A blind, prospective study on consecutive patients was designed. Overall, 174 subjects were included in the study: 88 (50.6%) in prostate cancer group, and 86 (49.4%) in control group. Electronic nose performance for prostate cancer was assessed using sensitivity and specificity. The diagnostic accuracy of electronic nose was reported as area under the receiver operating characteristic curve. Results: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 28 publications
1
19
0
3
Order By: Relevance
“…Asimakopoulos, Taverna, Talens, and Filianoti employed different electronic noses with and without neural network approaches to analyze urine samples and harvested sensitivities of 71.4%-85% and specificities of 79%-92.6%. [12][13][14][15] Waltman et al 16 used a different approach and used a novel electronic nose to examine exhaled breath. This resulted in a sensitivity and specificity of 84% each.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Asimakopoulos, Taverna, Talens, and Filianoti employed different electronic noses with and without neural network approaches to analyze urine samples and harvested sensitivities of 71.4%-85% and specificities of 79%-92.6%. [12][13][14][15] Waltman et al 16 used a different approach and used a novel electronic nose to examine exhaled breath. This resulted in a sensitivity and specificity of 84% each.…”
Section: Resultsmentioning
confidence: 99%
“…This is in keeping with previous research by other groups who also found limited accuracy when using electronic noses. Asimakopoulos, Taverna, Talens, and Filianoti employed different electronic noses with and without neural network approaches to analyze urine samples and harvested sensitivities of 71.4%–85% and specificities of 79%–92.6% 12–15 . Waltman et al 16 used a different approach and used a novel electronic nose to examine exhaled breath.…”
Section: Discussionmentioning
confidence: 99%
“…[60 ▪▪ ]and Capelli et al [33] assessed the accuracy of an electronic nose composed of MOS sensors and machine learning using pattern recognition techniques for early detection of prostate cancer. The sensitivity values reported were 85.2 and 82%, while the specificities were 79.1 and 87%, respectively [33,60 ▪▪ ].…”
Section: Urological Cancers and The Detection Of Volatile Organic Com...mentioning
confidence: 88%
“…Urine analysis via an e-nose has been shown to distinguish between PCa patients and healthy controls, according to their volatilome profiling. Filianoti et al [ 54 ], Taverna et al [ 92 ], Capelli et al [ 93 ], and Bannaga et al [ 94 ] used different methodologies based on urine analysis through e-noses ( Table 3 ) and proved that urine headspace and its modification are connected to cancer. In turn, Waltman et al [ 95 ] used an e-nose to distinguish between PCa patients and healthy controls, according to the volatilome profiling of exhaled breath.…”
Section: Contribution Of the Omics Sciencementioning
confidence: 99%